Ant predation of larval Diatraea saccharalis Fab. (Lep., Crambidae) in new sugarcane in Brazil - Rossi, M. N.; Fowler, H. G. (Wiley-Blackwell, 2000)
Ant predation of natural field populations of larval sugarcane borers, Diatraea saccharalis, was evaluated by using insecticidal check techniques, and through survivorship studies of artificial high-density infestations, in plantations in Brazil. Areas of ant suppression had higher levels of D. saccharalis than unsuppressed areas, although both types of areas normally had extremely low D. saccharalis populations. Artifical infestations of D. saccharalis yielded significantly lower larval survivorship in unsuppressed areas than in suppressed areas. Fire ants (Solenopsis spp.) were always the most abundant ant. This study has demonstrated that ants are important pest predators in Brazilian sugarcane fields.